2021
DOI: 10.1007/s12687-021-00537-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding genomic health information: how to meet the needs of the culturally and linguistically diverse community—a mixed methods study

Abstract: Clinical genomic testing, analysis of your entire genetic material for healthcare purposes, is a complex topic for various medical specialities. Although Australia is a multicultural society, most genomic resources are produced in English which can make understanding challenging for people from culturally and linguistically diverse (CALD) backgrounds. A mixed methods approach explored the views of healthcare interpreters and people from CALD backgrounds to identify knowledge gaps and inform the provision of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Both reviews and workshop discussions emphasised the importance of adapting research practices to the needs of different groups and designing accessible communication strategies that ensure critical information is conveyed clearly and effectively (Kobayashi et al, 2013 ; Campbell et al, 2017 ; Kraft and Doerr, 2018 ; Sabatello et al, 2019 ; Hendricks-Sturrup and Johnson-Glover, 2021 ; Uebergang et al, 2021 ; Garofalo et al, 2022 ). Such communication strategies were thought to improve the trustworthiness of research (Blanchard et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both reviews and workshop discussions emphasised the importance of adapting research practices to the needs of different groups and designing accessible communication strategies that ensure critical information is conveyed clearly and effectively (Kobayashi et al, 2013 ; Campbell et al, 2017 ; Kraft and Doerr, 2018 ; Sabatello et al, 2019 ; Hendricks-Sturrup and Johnson-Glover, 2021 ; Uebergang et al, 2021 ; Garofalo et al, 2022 ). Such communication strategies were thought to improve the trustworthiness of research (Blanchard et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants with English as an additional language were more likely to feel insufficiently informed, despite the use of interpreters in clinical consultations, as noted in other areas of healthcare [ 36 ]. Data-sharing decision-making may be impacted by the translation of information (e.g., the lack of appropriate translations for genomic vocabulary) and cultural differences [ 37 ]. Care must be taken that digital tools and other support for decision-making do not exacerbate inequalities or barriers to access.…”
Section: Discussionmentioning
confidence: 99%
“…Preferences for the type of health professional offering and providing polygenic risk information, and the nature of the educational and support resources, may also vary across diverse populations, cultural and linguistic groups, which was not explored in our study [ 40 ]. For example, a qualitative interview study with diverse Spanish- and English-speaking patients on the clinical use of polygenic risk scores for hypocholesterolemia showed that the majority of participants favored in-person disclosure, followed by electronic and telehealth delivery [ 41 ].…”
Section: Discussionmentioning
confidence: 99%